Multi-cancer detection of circulating tumor cells by targeting oncofetal chondroitin sulfate - Caroline Løppke; Randi Ugleholdt; Christine F. Secher; Nicolai T. Sand; Joana Mujollari; Tobias Gustavsson; Robert Dagil; Thor G. Theander; Ali Salanti; Kristoffer S. Rohrberg; Mette Ø. Agerbæk (npj Precision Oncology)
Abstract Liquid biopsies for the detection of circulating tumor cells (CTCs) are a promising strategy for personalized cancer management. However, traditional CTC detection platforms are often constrained to epithelial cancers, vulnerable to phenotypic changes, and rely on specialized devices for standardized detection, restricting the clinical utility across diverse cancer types and healthcare settings. In this study, we present a tumor-agnostic, platform-independent CTC detection strategy based on recognition of the cancer-specific glycosylation, oncofetal chondroitin sulfate (ofCS). Through coupling of the ofCS-binding protein, VAR2CSA, to a fluorophore-carrying dextran polymer, we successfully detected ofCS-positive CTCs from blood samples in two diverse and independent cohorts comprising early- and late-stage cancer patients of both epithelial and non-epithelial tumor origin. In addition, no ofCS-positive cells were detected in non-malignant controls. Thus, targeting of ofCS has the potential to expand the range of patients who could benefit from CTC analysis, enhancing the clinical utility in various cancer settings.